Comparative Analysis of piRNA Profiles Helps to Elucidate Cryoinjury Between Giant Panda and Boar Sperm During Cryopreservation - Wang, Yihan; Zhou, Yingmin; Ali, Malik Ahsan; Zhang, Jiaman; Wang, Wencan; Huang, Yan; Luo, Bo; Zhang, Heming; Qin, Ziyue; Zhang, Yan; Zhang, Ming; Zhou, Guangbin; et al. (Frontiers in Veterinary Science, 2021)
Cryopreservation induces sperm cryoinjuries, including physiological and functional changes. However, the molecular mechanisms of sperm cryoinjury and cryoresistance are still unknown. Cryoresistance or freeze tolerance of sperm varies across species, and boar sperm is more susceptible to cold stress. Contrary to boar sperm, giant panda sperm appears to be strongly freeze tolerance and is capable of surviving repeated cycles of freeze-thawing. In this study, differentially expressed (DE)piRNAs of fresh and frozen-thawed sperm with different freeze tolerance capacity from giant panda and boar were evaluated. The results showed 1160 (22 down-regulated and 1138 up-regulated) and 384 (110 up-regulated and 274 down-regulated) differentially expressed (DE) piRNAs were identified in giant panda and boar sperm, respectively. Gene ontology (GO) enrichment analysis revealed that the target DE mRNAs of DE piRNAs were mainly enriched in biological regulation, cellular and metabolic process in giant panda and boar sperm. Moreover, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated that the target DE mRNAs of DE piRNAs were only distributed on DNA replication and cAMP signaling pathway in giant panda, but cAMP, cGMP and MAPK signaling pathway in boar sperm were considered as part of olfactory transduction pathway. In conclusion, we speculated that the difference of piRNA profiles and the DE piRNAs involved in cAMP signaling pathway in boar and giant panda maybe contributed to different freeze tolerance capacity between giant panda and boar sperm, which helps to elucidate the molecular mechanism behind sperm cryoinjury and cryoresistance.